TALENT MANAGEMENT IN SUPPORTING THE RATIONALIZATION OF CIVIL SERVICE (ASN) CAREER DEVELOPMENT MANAGEMENT AT THE MINISTRY OF MARINE AFFAIRS AND FISHERIES REPUBLIC INDONESIA - Yuliana, Muammar; Sutrisno, Edy; Asropi, Asropi (Universitas Negeri Yogyakarta, 2023)
This paper is conducted to analyze the rationalization of career development management through talent management policies. This paper uses qualitative methods and a descriptive approach. This research was conducted at the Ministry of Marine Affairs and Fisheries of the Republic of Indonesia (MMAF RI) which consistently applies talent management in supporting career development. The results showed that managing career development through talent management schemes is very important for personnel apparatus and HR management in achieving organizational and individual career goals. Civil services consider that talent management schemes can help them obtain better and structured career development. Meanwhile, the HR management apparatus views the talent management scheme as a tool to improve organizational performance and develop the competence of civil services. The study also shows that MMAF RI must implement several strategies to ensure the success of talent management schemes. These strategies include involving civil services in the career development process, providing relevant and consistent training and development, and providing constructive and ongoing feedback to civil servants. Career development through talent management schemes is very important for personnel apparatus and HR management in achieving organizational and individual career goals. This paper recommends MMAF RI adopt an integrated apparatus HR management strategy to ensure the success of the talent management scheme and improve overall organizational performance.